RELIGIUSITAS DAN KONSTRUKSI KOMUNIKASI TRANSENDENTAL TUNANETRA - Kadri, Kadri (JURNAL PENELITIAN KEISLAMAN, 2010)
This qualitative research using phenomenological approach examines transcendental communication of the blind who lose sight in their adulthood. The research shows that one who loses sight during his/her adulthood will undergo a dramatic change not only in their outward biological and psychological aspects but also in their transcendental communication with God. Regarding transcendental communication, this study reveals three different models of attitudes of the blind. The first attitude begins with the emergence of spiritual awareness that consciously admits the self and God existence. The blindness stimulates a better change in the blindâs style and form of transcendental communication even though each respondent discloses a different pattern of change, resulting type âAâ that represents a minimun change to type âFâ that represents maximum change. Based on all dynamic of transcendental communication made by the respondents, the research underscores four models of religious identity of the blind; formal religious, temporal religious, religious and very religious. All these models represent distinct transcendental communication both qualitatively and quantitatively.